Computer simulation of platelet activation in a pulsatile ventricular assist device, through finite elements and a simplified geometry - Fries, Exequiel (2017)
Ventricular assist devices are a technological solution for patients who suffer from cardiac insufficiency and await a transplant. In this work, a new design of an implantable pulsatile blood pump is analyzed in terms of blood damage, by means of finite elements on a simplified geometry. It is a double effect volumetric pump, which has a noncontact driven piston and four active valves. The analysis is done by means of blood flow simulation into the pump and the prediction of platelets activation. The last is a measure of the pump compatibility with human life.The platelet activation state is evaluated by an equivalent or representative shear stress and compared with bibliographic data corresponding to other VAD kinds and cardiac prosthetic valves. The results show that, for the complementary blood flow rate supplied by the simulated VAD, the predicted platelet damage is in the same levels of current cardiac devices, particularly other VADs.